Respuesta :
y=4x-9
y=x-3
-4x + y = -9
-x +y = -3 //-1
-4x + y = -9
x - y = 3
---------------------
-3x = -6
x = 2
y = 2-3
y = -1
Answer:
(2, -1)
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
- Equality Properties
Algebra I
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
Step 1: Define systems
y = 4x - 9
y = x - 3
Step 2: Solve for x
- Substitute in y: 4x - 9 = x - 3
- Subtract x on both sides: 3x - 9 = -3
- Add 9 to both sides: 3x = 6
- Divide 3 on both sides: x = 2
Step 3: Solve for y
- Define: y = x - 3
- Substitute in x: y = 2 - 3
- Subtract: y = -1